Review Of Electricity Subsidies In Indonesia 2015-2020 - Hanan, Naufal Noor; Fuady, Muhammad Syahrul (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
To meet the adequacy of electricity needs and help people's purchasing power, the government through the State Revenue and Expenditure Budget (APBN) provides cheap and affordable electricity services for certain segments of society every year. Electricity subsidies are assistance provided by the government to consumers in the form of electricity tariffs that are lower than their economic tariffs. The difference between the subsidized tariff and the economic tariff is borne by the Government, which is then paid to PT Perusahaan Listrik Negara (PT PLN Persero). This research will review the burden of subsidy spending that must be borne by the government and the journey of electricity subsidy reform on target. In addition, it will also review the role of electricity as an instrument in handling COVID-19 in 2020. Based on data on the realization of electricity subsidy spending for the last 5 years which have been audited (2015-2020), it can be seen that starting in 2015 there was a decline in spending as policy reforms began. more targeted electricity subsidies. However, since 2018 electricity subsidies have again increased due to one of the reasons for the increase in the cost of providing electricity (BPP) of electricity in FY 2018 compared to FY 2017 and a significant increase in the number of 450 VA customers. In 2020, an increase in electricity subsidies also occurred due to the electricity discount policy for certain groups of people and business entities as part of handling the impact of COVID-19.